2020
DOI: 10.3389/fmed.2020.589825
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Ammonia in Critical Care Patients Without Known Hepatic Disease

Abstract: Background and Aims: Hyperammonemia usually develops because of hepatic disease, but it may occur in patients with non-hepatic hyperammonemia (NHH). But, studies on the prognosis and possible risk factors of this disorder are lacking. The aim of this study was to find possible prognostic and risk factors for NHH in critically ill patients. Methods: Data were extracted from MIMIC III Database. Survival was analyzed by the Kaplan-Meier method. Univariate and multivariate analyses were performed to identify progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A retrospective analysis of a multicenter database demonstrated some common metabolic disturbances and acute renal failure as potentially modifiable factors contributing to SAE ( 13 ). Another study from our center found that nonhepatic hyperammonemia occurred more often in patients with SAE ( 30 ), and this may be a potential therapeutic target for SAE ( 31 ).…”
Section: Discussionmentioning
confidence: 89%
“…A retrospective analysis of a multicenter database demonstrated some common metabolic disturbances and acute renal failure as potentially modifiable factors contributing to SAE ( 13 ). Another study from our center found that nonhepatic hyperammonemia occurred more often in patients with SAE ( 30 ), and this may be a potential therapeutic target for SAE ( 31 ).…”
Section: Discussionmentioning
confidence: 89%
“…Acquired diseases can be further divided into hyperammonemia because of hepatic and nonhepatic causes. Congenital disorders associated with enzyme defects include UCDs, organic acidosis, congenital lactic acidosis, fatty acid oxidation defects, and dibasic amino acid deficiency ( Savy et al, 2018 ; Zhao et al, 2020 ). Ammonia is normally produced in the large and small intestines, where it is carried to the liver and converted into urea via the urea cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In congenital metabolic disorders including hyperammonemia, secondary ammonia formation occurs when there is a defect in ammonia-detoxifying enzymes [e.g., in urea cycle disorders (UCDs)] or when there is liver damage (e.g., in cirrhosis) ( Savy et al, 2018 ; Zhao et al, 2020 ). Consequently, this process leads to the accumulation of ammonia (a toxic metabolite), which enters the portosystemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…( 25 (30,31) In the present research, we examined whether there could be differences in the different prognosis between distinct types of diseases (e.g., Sepsis, Kidney failure), and no signi cant differences were identi ed, consistent with previously reported results in severity of hyperammonemia. (17) This may be attributed to the diverse and complicated etiology of NHH, which indicating the prognosis. Overall energy expenditure and severity of disease are the key factors contributing to the occurrence of NHH.…”
Section: Discussionmentioning
confidence: 99%
“…(14)(15)(16) Two recent retrospective studies demonstrated that serum ammonia status was an independent prognostic predictor of mortality for NHH patients. (7,17) Speci cally, proactive monitoring of blood ammonia levels for the prompt detection of, and early intervention against, NHH may improve the prognosis of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%